2014
DOI: 10.1517/14740338.2014.926887
|View full text |Cite
|
Sign up to set email alerts
|

Commonly used diabetes and cardiovascular medications and cancer recurrence and cancer-specific mortality: a review of the literature

Abstract: Metformin and aspirin were associated with a reduced risk of cancer recurrence and cancer-specific mortality. The evidence for statins and antihypertensive medications on cancer survival was inconsistent. There were few studies to suggest that any of the medication classes of interest were associated with negative effects on cancer survival. Methodological shortcomings within observational studies, such as confounding, distinguishing between use of medications pre-cancer versus post-cancer diagnosis/treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 154 publications
(261 reference statements)
1
14
0
Order By: Relevance
“…Notably, in the United Kingdom Prospective Diabetes Study (UKPDS), metformin use, compared with other antidiabetic drugs, decreased the risk of cardiovascular disease (Group, 1998), cancer incidence and overall mortality (Wu et al ., 2014), and possibly cognitive decline (Ng et al ., 2014). Safety has been established and the pro-longevity effects noted would argue for testing the use of metformin in humans.…”
Section: Activators Of the Ampk Pathwaymentioning
confidence: 99%
“…Notably, in the United Kingdom Prospective Diabetes Study (UKPDS), metformin use, compared with other antidiabetic drugs, decreased the risk of cardiovascular disease (Group, 1998), cancer incidence and overall mortality (Wu et al ., 2014), and possibly cognitive decline (Ng et al ., 2014). Safety has been established and the pro-longevity effects noted would argue for testing the use of metformin in humans.…”
Section: Activators Of the Ampk Pathwaymentioning
confidence: 99%
“… 55 Additionally, there are also many studies that focus on whether antiaging effects of metformin can be demonstrated in patients with T2DM. In the United Kingdom Prospective Diabetes Study (UKPDS), the use of metformin decreased the risk of cardiovascular disease, 56 cancer incidence and overall mortality, 57 compared with other antidiabetic drugs. Furthermore, a large retrospective observational study including over 180,000 subjects showed that patients with T2DM initiated with metformin monotherapy had longer survival than did matched, non-diabetic controls; however, in this study they did not investigate for a dose-response association.…”
Section: Antiaging Effect Of Metforminmentioning
confidence: 99%
“…Over the last decade, epidemiologic studies have indicated that use of β-blockers may have beneficial effects on cancer progression, metastasis, and mortality ( 15 24 ). β-blockers form a group of commonly prescribed drugs used as treatment for hypertension, cardiac heart failure, and arrhythmias, as well as for migraine prophylaxis.…”
Section: Introductionmentioning
confidence: 99%